Larangan Penggunaan Wangi-Wangian Bagi Wanita: Studi Takhrij dan Syarah Hadis - Ramdan; Hidayatul Fikra; Asep Saeful Mimbar (UIN Sunan Gunung Djati Bandung, 2022)
The study aims to examine the hadith on the prohibition of fragrances for women contextually. This study was conducted by looking for and comparing similar hadiths, considering the historical context and the purpose or maqashid of the hadith. The method used in this research is a qualitative method with library research and analysis through takhrij and sharah hadith. From this research, it can be concluded that the hadith of Imam Tirmidhi No. 2710 on the prohibition of women wearing perfumes has a shahih quality, so it is accepted maqbul and can be practiced (ma'mul). From the sharah of hadith, it is known that hadith that is understood textually is different from hadith that is understood contextually. Regarding the hadith on the prohibition of fragrances for women if interpreted textually becomes irrelevant in this day and age because perfume is part of the cleanliness of the body although in its use it is forbidden to excessive. The study recommends further research with different methods and contemporary analysis that are more relevant to current circumstances.